(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
An experiment was conducted at Hudeiba Research StationFarm during the winter seasons of 2004/05, 2005/06 and 2006/07 to studythe effect of cutting system and time of nitrogen application on forageyield of barley. The experiment was executed in split plot design withthree replications; the times of nitrogen application were assigned to themain plots and the cutting systems to the subplots. Four nitrogenapplications: at sowing, 15, 30 and 45 days from sowing (DAS) and fourcutting systems: a single cut of the primary crop (SC) and three doublecuts referred to as DC1, DC2 and DC3 were studied. The primary cropsof the SC were cut at the milk stage, while those of the double cuts werecut at the age of 30, 45 and 60 DAS for DC1, DC2 and DC3, respectively,and the secondary cut in each double cut was at the milk stage. Comparedwith the SC system, the three DC systems prolonged the growing seasonbut significantly reduced the dry matter yields even in the cumulative ofboth cuts. The DC systems increased the tiller densities, but reduced theplant densities and the total culm densities of the secondary crops. Interms of the cumulative yields of the DC systems, DC1outyielded theother DC systems. The time of nitrogen application did not affect theforage yield.